Structural and functional studies of low-CO2 inducible protein LCIB homolog from phaeodactylumtricornutuminvolved in CO2-concentrating mechanism - Luo, Yuanyuan (2017)
Global warming and food crisis urge us to improve global productivity. However, photosynthesis is limited by poor efficiency and specificity of Ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). Many organisms develop CO2-concentrating mechanisms (CCMs) to maintain high CO2 concentration near Rubisco. The low-CO2 inducible B protein (LCIB) in Chlamydomonasreinhardtii was found to bear close structural resemblance to classic beta-type carbonic anhydrase (CA) which plays an important role in CCM. Its homolog in diatom PhaeodactylumtricornutumPtLCIB4 showed significantly increased CA activity with addition of Copper ion. With the aim to study the influence of Cu2+ on its structure and function, PtLCIB4 was expressed as a recombinant protein in E.coli and purified by nickel affinity chromatography and size exclusion chromatography. Crystallization screening was performed on the purified protein which was further co-crystallized and soaked with CuCl2. The crystal structure of PtLCIB4-Cu was obtained by X-ray diffraction with resolution up to 2 Å. No significant difference was observed after superimposing its crystal structure with copper-freePtLCIB4. Thus, hypothesis of facile metal ion exchange between copper and zinc in the active site of PtLCIB4 was proposed which need to be verified by fluorescence scanning at synchrotron radiation facility. Remove